Analysis of students' learning difficulties in mathematics on the concept of mixed devotion materials (Indonesian Institute for Counseling, Education and Theraphy, 2023)
The background of this research stems from the phenomenon of many students who still have difficulties in understanding the concept of fractions because they are unable to apply mathematical concepts correctly, especially in Class V SDN Kebon Jeruk 06, where these learning difficulties become obstacles in learning mathematics. The problem in this study is how the phenomenon of mathematics learning difficulties in fraction concept material that occurs in grade V students of SDN Kebon Jeruk 06 caused by learning difficulties. Descriptive qualitative research method was used in this research. The data collection methods used were observation, interviews, tests, and documentation. Data reduction, data presentation, and conclusion drawing were used in the data analysis process. The results of this study are learning difficulties in mathematics subjects on the concept of mixed fraction material experienced by students, including students' lack of understanding in using the concept of fractions, students' lack of skills in counting and students' lack of understanding of problem solving on story problems. The phenomenon that occurs in mathematics learning difficulties in the concept of fraction material in class V SDN Kebon Jeruk 06 is marked by the low scores of students who get an average score of 39.2 on the test questions, this is due to the absence of students' interest in learning fraction material and students' boredom with learning media that only use the lecture method in teaching fraction concept material so that it does not bring student activeness.